INNOVATION MANAGEMENT MODEL TO IMPROVE CORPORATE INNOVATION PERFORMANCE - Santoso, Aloysius Budi; Irawan, Agustinus Purna; Suhartanto, Eko (International Journal of Application on Economics and Business, 2024)
Entering the industrial era 4.0, technology continues to develop and is used to improve company performance. This emphasizes the occurrence of disruption between companies which is mainly driven using this technology. Previous studies have emphasized the importance of innovation to overcome this condition. Astra Group as one of the conglomerate groups in Indonesia has understood and implemented this consistently and persistently. For this reason, the innovation management model in this group is important to be investigated further to provide understanding and scientific contributions related to innovation management in corporations. From the literature, at least three important factors were found in the management of innovation, namely 1) managerial capabilities, 2) adhocracy culture, and 3) knowledge sharing on innovation capabilities and performance in this group. The findings may contribute to an opportunity for researchers to confirm this model in future research.